Dinuclear thiazolylidene copper complex as highly active catalyst for azid-alkyne cycloadditions - Schöffler, Anne; Makarem, Ata; Rominger, Frank; Straub, Bernd Franz (Beilstein journal of organic chemistry, 2016)
Beilstein Journal of Organic Chemistry